تجربة أسلمة المعرفة في الجامعة الإسلامية العالمية بماليزيا: اتجاهات طلبة الجامعة نحو فعاليتها = The implementation of Islamization of knowledge at the International Islamic University Malaysia (IIUM): students’ perceptions of its effectiveness - Rasidik, Nurul Nahirah; Samae, Abdulhalim (Academy of Islamic Studies, UM, 2025)
إن قضية أسلمة المعرفة ليست قضية جديدة، وإنما هي قضية تهتم بها الجامعة الإسلامية العالمية بماليزيا منذ تأسيسها عام 1983م. وقد بذلت جهود كبيرة لتحقيق أهداف التكامل بين القيم الإسلامية والمعرفة الحديثة من خلال المناهج الدراسية، والأنشطة الطلابية، وأساليب متعددة. ورغم تعدد الدراسات حول تجربة أسلمة المعرفة في هذه الجامعة، إلا أن هناك فجوة معرفية تتعلق باتجاهات طلبة الجامعة نحو فاعلية هذه التجربة. ولذلك، تهدف هذه الدراسة إلى تحليل اتجاهات طلبة الجامعة الإسلامية العالمية بماليزيا نحو فاعلية تجربة أسلمة المعرفة فيها. وتم جمع البيانات حول اتجاهات طلبة من خلال توزيع الاستبانة على 55 طالبا في كلية السياحة المستدامة واللغات المعاصرة بالجامعة الإسلامية العالمية بماليزيا فرع باجوه. وقد توصلت الدراسة إلى عدد من النتائج المهمة، ومن أبرزها؛ أولا، وجود مستوى عال من الوعي لدى الطلبة بأهمية تجربة أسلمة المعرفة في الجامعة الإسلامية العالمية بماليزيا، مما يدل على نجاح الجامعة في ترسيخ مفهوم أسلمة المعرفة لدى الطلبة. ثانياً، تأثير أسلمة المعرفة على حياة الطلبة حيث إنهم يدركون أهمية التمسك بالقيم الإسلامية في كل ما تعلموها من المناهج الدراسية. ثالثًا، تعتمد فاعلية أسلمة المعرفة بشكل كبير على فهم المحاضرين لهذا المفهوم ونهجهم في تطبيقه أثناء التدريس. وفي ضوء هذه النتائج، توصي الدراسة بإجراء دراسات مستقبلية تركز على تقييم مدى فهم المحاضرين لمفهوم أسلمة المعرفة وطرق تطبيقها في قاعة الدرس. ***** The issue of Islamization of Knowledge is not a new issue; rather, it has been a central focus of the International Islamic University Malaysia (IIUM) since its establishment in 1983. Significant efforts have been made to achieve the goal of integrating Islamic values with modern knowledge through academic curricula, student activities, and various approaches. While numerous studies have examined the experience of Islamization of Knowledge at IIUM, there remains a notable gap concerning students’ perceptions of the effectiveness of this implementation. Therefore, this study aims to analyze IIUM students’ perceptions towards the effectiveness of the implementation of Islamization of Knowledge at the university. Data were collected through a questionnaire distributed to 55 students from the Kulliyyah of Sustainable Tourism and Contemporary Languages, IIUM Pagoh Campus. The findings reveal several important results: first, students demonstrated a high level of awareness regarding the significance of the Islamization implementation, indicating the university’s success in promoting the concept among its students. Second, Islamization has an impact on students’ lives, as they expressed a strong sense of commitment to upholding Islamic values in all academic content learned. Third, the effectiveness of the Islamization process largely depends on lecturers’ understanding of the concept and their approach to integrating it in teaching. In light of these findings, the study recommends future research to assess lecturers’ level of understanding and implementation of the Islamization of Knowledge within the classroom context.